Solving the Functional Equation f(x+y)=f(x)f(y)

preview_player
Показать описание
If you need to post a picture of your solution or idea:
#ChallengingMathProblems #FunctionalEquations

EXPLORE 😎:

PLAYLISTS 🎵 :

Рекомендации по теме
Комментарии
Автор

Me: sees the thumbnail, my subconscious mind: a^x!

govindam_adi_purusham
Автор

Once you reach f(x) = m e^(c x), you can use f(0) = 1 to see immediately that m = 1 is the only (non-zero) choice. :)

davidblauyoutube
Автор

Directly differentiate both sides taking y as constant you will get f'(x+y)=f'(x)f(y) Now put x=0 and y=x you will get f'(x)=f'(0)f(x) now proceed with the video

BCS-IshtiyakAhmadKhan
Автор

This style of problems is my favorite, not insanely complex but just tricky enough to be intriguing. Great job!

Darkev
Автор

It's like re-watching your favorite movie: I know where it's going but it's still fun to watch it get there. Great video!

idavid
Автор

I never knew about these types of problems. Functional equations are my new favourite thing. You could easily see that e^Cx is a solution for f(x), but doing it rigorously revealed that it is the only solution (apart from the trivial case).

bscutajar
Автор

I enjoy this problem because it can even be offered to strong algebra students, who can be challenged to think deeply about the operations.
Set y = 0... f(x+0) = f(x) • f(0). So either f(x) = 0 or you can divide by f(x) to get f(0) = 1.
Set y = 1... f(x+1) = f(x) • f(1). So f has a constant factor of change, whatever value f(1) is.
A function with a constant factor of change — that's what exponential functions are all about!
So f(x) = 1 • f(1)^x.
(One can rewrite the value f(1) other ways, say, b or e^k.)

dennisdesormier
Автор

f(x + y) = f(x) * f(y)

First, by exchanging x by y, we get exactly the same expression. This allows us to conclude that the expressions for f(x) and f(y) have exactly the same form. Also, making x = 0, it follows that f(y) = f(0) * f(y), that is, f(0) = 1.
Differentiating both sides with respect to x (using the product rule on the right side of the equality):

df(x+y)/dx = f(x) * df(y)/dx + f(y) * df(x)/dx

Using the starting equation:

df(x+y)/dx = [ f(x + y)/f(y)] * df(y)/dx + [f(x + y)/f(x)] * df(x)/dx

[1/f(x + y)] * df(x+y)/dx = [1/f(y)] * df(y)/dx + [1/f(x)] * df(x)/dx

Since f(y) is not a function of x, df(y)/dx = 0. Therefore:

[1/f(x + y)] * df(x+y)/dx = [1/f(x)] * df(x)/dx

Since x and y are independent, the only way for equality to hold is if both sides of the equation are a constant (k). So:

[1/f(x)] * df(x)/dx = k

df(x)/f(x) = k * dx

Integrating both sides, we get:

f(x) = A e^kx

Since f(0) = 1, we have A = 1. Therefore, f(x) = e^kx.

walterufsc
Автор

Wow how a functional equation ends up with the definition of derivative 😍

tonyhaddad
Автор

The highlight is f(0)=1, which is used to express f’(0). SO COOL👍

josephsun
Автор

We can let e^c=b for some b>0 and then e^cx=(e^c)^x=b^x
Which we can combine with the solution f(x)=0 to say the solution is
f(x)=b^x for b greater than or equal to 0

Happy_Abe
Автор

After seeing the live chat, I realize that I messed up and did not follow the plan. Today should be a radical equation so we'll have to switch today and tomorrow and we'll do the radical equation tomorrow! Sorry for the confusion
EDIT: The post has been edited to reflect the changes!

SyberMath
Автор

Hello, @SyberMath I deduced that f(x)=0 for all real x. This, being a constant function, is differentiable for all real x.

titassamanta
Автор

We don't need e, indeed. f(x)=c^x is the solution for any arbitrary constant c>0. Let's check: f(x+y)=f(x)f(y) -> c^(x+y)=(c^x)(c^y) -> c^(x+y)=c^(x+y)

fatihsinanesen
Автор

classical properties of exponential function as for logarithm (reciprocal function of exponential) f(xy) = f(x) + f(y)

WahranRai
Автор

Thankyou so much I had been searching for same time for about 30 min.😊

TarunRanga
Автор

Wow that's a really cool solution :0
I've only known this problem with the given that is continuous, not differentiable. It's a much longer solution if we don't assume differentiability.

skylardeslypere
Автор

Thank you I actually was trying to find how to solve such problems.

prasham_shah
Автор

f(x) = 1 for all x, also solves this equation. So there are two trivial solutions.

ryanburkett
Автор

In fact the solution of this functional equation is obvious: f(x) = exp(x), what can be easily verified by substitution exp(x) to the equation. But the result may be achieved by more strong approach.
1) f(x) never can be negative, what follows from partial case y = x, so f(2x) = f(x)^2 > or = 0
2) f(x) is not 0 for either value of argument, except of the trivial case f(x)=0 for all x.
This follows from modified equation
f(z) = f(x) • f(z - x)
So if f(x) = 0 for some x, then f(z)=0 for all z
3) From anothe partial case y=0 we can find f(0):
f(x) = f(x) • f(0)
so f(0) = 1 except the trivial case
4) let's logarithm both sides of equation. We may do this because f(x) > 0
ln(f(x+y) = ln(f(x)) + ln(f(y))
Denoting g(x) = ln(f(x)) we'll get
g(x+y) = g(x) + g(y)
and the only solution of this equation is a linear function f(x)=x

Hobbitangle